Revisiting the educational effects of fetal lodine deciency - Niklas Bengtsson; Stefan Peterson; Fredrik Sävje (Uppsala University, Department of Economics, 2013)
Recent research has reported positive effects on schooling due to in utero protection from iodine deficiency resulting from iodized oil capsule distribution in Tanzania. We revisit the Tanzanian experience by investigating how these effects differ over time and across surveys; across different treatment specifications; and across additional educational outcome measures. Contrary to previous studies, we find that the estimated effects tend to be small and not robust across specifications or samples. Using all available data and a medically motivated iodine depletion function, we find no evidence of a positive long-run effect of iodine deficiency protection on educational attainment.
urn:nbn:se:uu:diva-211571
Keywords: I12; I21; J16; O15; 330; Iodine deficiency; Education; Prenatal exposure; Multiple outcomes; Replication; Field; Robles and Torero